Improving the Ability of Fifth-Grade Students to Sing Regional Songs Through Audiovisual Media Using the Card Sort Method at SD Inpres Binangga - Nur Safia; Yun Ratna Lagandesa; Sisriawan Lapasere; Muhammad Aqil; Rangga Putera Boroallo (Journal of Educational Sciences, 2026)
This study aimed to improve the regional song singing ability of fifth-g,rade students at SD Inpres Binangga through the integration of audiovisual media and the Card Sort method. The study was motivated by students’ low singing performance caused by conventional teaching practices, limited use of instructional media, and low learning engagement. This research employed Classroom Action Research based on the Kemmis and McTaggart model, consisting of two cycles with the stages of planning, action, observation, and reflection. The participants were 12 fifth-grade students in the 2025/2026 academic year. Data were collected through observation, performance tests, and documentation and analyzed using descriptive quantitative and qualitative techniques. The findings revealed continuous improvement in students’ singing ability across the research cycles. The average score increased from 58.3 in the pre-cycle to 72.5 in Cycle I and 84.2 in Cycle II, while classical learning mastery improved from 25% to 66.7% and finally reached 91.7%, exceeding the predetermined success criterion. The integration of audiovisual media and the Card Sort method also enhanced students’ participation, confidence, and collaborative learning. Therefore, this instructional approach is effective in improving elementary students’ regional song singing ability and can serve as an innovative strategy for music learning.